Examining Legal Precedents and Social Implications - Interplay Between Intellectual Property Rights and Digital Piracy in the Age of DMCA - Rafli, Zulkifli (Moccasin Journal De Public Perspective, 2024)
This study offers a comprehensive examination of the complexities surrounding digital piracy and copyright enforcement in the contemporary digital landscape, with a particular focus on the implications of the Digital Millennium Copyright Act (DMCA). Through a multi-method approach encompassing document analysis, semi-structured interviews, case studies, and illustrative examples, the study delves deep into legal frameworks, socio-cultural dynamics, and technological advancements shaping the digital copyright landscape. Findings reveal nuanced insights into the challenges and opportunities for addressing digital piracy while preserving innovation, creativity, and equitable access to digital content. Key recommendations for policymakers, legal practitioners, industry stakeholders, and researchers are provided to inform evidence-based interventions and future research endeavors in the field of digital copyright enforcement.